1994
DOI: 10.1093/carcin/15.10.2087
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen: evidence by 32P–postlabeling and use of metabolic inhibitors for two distinct pathways leading to mouse hepatic DNA adduct formation and identification of 4–hydroxytamoxifen as a proximate metabolite

Abstract: Exposure to pentachlorophenol (PCP) strongly intensifies the formation of mouse hepatic DNA adducts elicited by oral administration of tamoxifen (TAM), as previously shown by 32P-postlabeling. To explain this effect, PCP was proposed to interfere with the detoxication by sulfate conjugation of an as yet unidentified hydroxylated proximate TAM metabolite. A comparison of the present and earlier results shows that the hepatic TAM adduct pattern in female ICR mice depended on the route of administration of TAM (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…α-Hydroxylation, epoxidation and generation of a quinone methide have all been presented as likely candidates (22,(42)(43)(44) but α-hydroxylation is considered to be the major pathway in rat liver (34). The key step in the mechanism of DNA adduct formation from α-hydroxytamoxifen is thought to involve the reversible O-sulphonation of the hydroxyl moiety generating a highly reactive carbocation (30,45). In support of this, experiments using 32 P-post-labelling of DNA have shown that α-sulphate cis-tamoxifen is highly reactive to DNA, yielding up to 1600 times the number of DNA adducts obtained from α-hydroxytamoxifen (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…α-Hydroxylation, epoxidation and generation of a quinone methide have all been presented as likely candidates (22,(42)(43)(44) but α-hydroxylation is considered to be the major pathway in rat liver (34). The key step in the mechanism of DNA adduct formation from α-hydroxytamoxifen is thought to involve the reversible O-sulphonation of the hydroxyl moiety generating a highly reactive carbocation (30,45). In support of this, experiments using 32 P-post-labelling of DNA have shown that α-sulphate cis-tamoxifen is highly reactive to DNA, yielding up to 1600 times the number of DNA adducts obtained from α-hydroxytamoxifen (31).…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen is metabolized variously via primary N-demethylation, 4-hydroxylation, α-hydroxylation and N-oxidation ( Figure 1) by hepatic microsomes and cell lines (19)(20)(21)(22)(23), and additionally via secondary O-glucuronidation in hepatocytes (24) and in vivo (25)(26)(27)(28)(29), Ndemethylation being the principal biotransformation in humans and human liver microsomes (20,23,28). Both aromatic hydroxylation and α-hydroxylation have been consistently implicated in the formation of reactive tamoxifen metabolites in vitro and in experimental animals, and they appear to represent the initial steps of distinct bioactivation pathways in vivo (16,30). Although α-hydroxytamoxifen reacts directly, if slowly, with isolated DNA (31), both it and the chemically unreactive 4-hydroxytamoxifen are regarded as precursors of DNA-binding derivatives that have yet to be identified as metabolites, namely α-esters such as the highly reactive α-sulphate tamoxifen (31,32) and 4-hydroxytamoxifen quinone methide (33), respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA adducts are detected in mouse liver following oral (8)(9)(10) and i.p. (11) dosing, but are present at lower levels than similarly treated rats (10). With long-term dietary exposure (~40 mg tamoxifen/kg per day) adducts are present in mouse liver at 3 months (~67 adducts/ 10 8 nucleotides), but decrease with time and are not detectable in tamoxifen-treated mice by 2 years (10).…”
Section: Introductionmentioning
confidence: 99%
“…More important, the fact that several nonmutagenic carcinogens have been found to be carcinogenic in experimental animals as well as in humans (e.g., benzene, 2,3,7,8-tetrachlorodibenzo-p-dioxin [ (8). An extensive literature base shows that tamoxifen forms DNA adducts in the livers of rats, mice, and hamsters (9,10); it is activated to form DNA adducts by rat or human liver microsomes (11); it is dastogenic in human lymphoblastoid cells (12); and liver tumors in rats treated with tamoxifen have a high frequency of p53 mutations (13). These genotoxic activities demonstrate that tamoxifen does not act simply as tumor promoter.…”
Section: Introductionmentioning
confidence: 99%